Synthetic routes to iron chalcogenide nanoparticles and thin films. Issue 47 (21st November 2016) - Matthews, Peter D.; Akhtar, Masood; Malik, M. Azad; Revaprasadu, Neerish; O'Brien, Paul
Abstract : This perspective summarises the key synthetic routes to iron chalcogenide thin films/nanoparticles by highlighting the key aspects that lead to control over phase/morphology. Abstract : Iron chalcogenides are earth abundant, cheap and environmentally benign materials that have seen extensive research directed toward a range of applications, most notably for photovoltaics. The most common forms of materials for these applications are either nanoparticles or thin films. This perspective seeks to summarise the key synthetic routes to these materials by highlighting the key aspects that lead to control over phase and morphology.